The Correlation between Pack-Years of Smoking and Disease Activity, Quality of Life, Spinal Mobility, and Sacroiliitis Grading in Patients with Ankylosing Spondylitis - Sasan FALLAHI; Ahmad Reza JAMSHIDI; Farhad GHARIBDOOST; Mahdi MAHMOUDI; Nooshin AHMADZADEH; Mohammad Hossein NICKNAM3 (Archives of Rheumatology, 2013)
Objectives: This study aims to investigate the correlation between the pack-years of smoking and disease activity, quality of life, spinal mobility, and sacroiliitis grading and ankylosing spondylitis (AS) in Iranian patients with AS. Patients and methods: A total of 160 AS patients were evaluated according to their smoking status and pack-years of smoking. The outcome measures were disease activity, quality of life, spinal mobility, and sacroiliitis grading, and these were assessed by the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Ankylosing Spondylitis Quality of Life (ASQoL), Bath Ankylosing Spondylitis Metrology Index (BASMI), and radiography, respectively. Results: The smoking quantity was significantly higher in the patients with severe sacroiliitis than those with mild or moderate disease (p=0.001). A univariate analysis revealed an association between the pack-years of smoking and the BASDAI [regression coefficient (B)=0.05, standard error (SE)=0.02, 95% CI: 0.006 to 0.10; p=0.03], ASQoL (B=0.15, SE=0.06, 95% CI: 0.04 to 0.26; p=0.007), and BASMI (B=0.05, SE=0.02, 95% CI: 0.006 to 0.08; p=0.03). A multivariate analysis revealed a significant association between the packyears of smoking and the BASDAI and ASQoL. Conclusion: An independent correlation between smoking quantity with disease activity and quality of life was confirmed in a group of Iranian AS patients. There was also a relationship between smoking quantity and spinal mobility, however, it was dependent on other related factors. Patients who smoke should be encouraged to quit or smoke less to achieve a better outcome.